Under the Flint Hill Sky: Reflections on the Legacy of Annie Jump Cannon - DeWayne Backhus (Symphony in the Flint Hills, 2019)
Introduction: Our ancestors sought solace—inner peace or comfort—by looking up. Sometimes the look was purely spiritual, the desire to commune with something larger than the individual. And other times it was surely to reflect on what is out there and our relationship to that larger context.